The Creativity And Motif of Tetuko Written Batik In Nganjuk Regency - Yekti Herlina (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
Nganjuk regency is known for its textile craft with itscharacteristics called Nganjukbatik. Nganjuk batik has some unique motifs such as the Ajuk Ladang, Sera Rumput, Sido Mukti Tungkak, Sundut Sate, Acacia Flower Tumpal, and Rambutan Flower Tumpal.These motifs are usually worn in any formal and informal events.Tetuko written batik of Nganjuk Regency as one of the sub-sectors of the creative industry is createdbased on local wisdom or the nation's cultural heritage. The creativity inmaking and developing this batik is needed to produce competitive and high-quality products. Thus, this study aims at determining the creativity and motifs of Tetuko written batik used during the batik-making process. It was done by employing a descriptive qualitative and experiment along with observation, interview, and documentation. The targets of conducting this study are to provide a contribution, inspiration, and innovation to encourage creative and critical thinking ability related to creativity and motifs in Tetuko written batik of Nganjuk Regency. It is expected that this batik appealsto more people and becomes a high-quality product.